Thermosensitive injectable hydrogel based on chitosan-polygalacturonic acid polyelectrolyte complexes for bone tissue engineering. (15th October 2022) - Wasupalli, Geeta Kumari; Verma, Devendra
Abstract: An extracellular matrix (ECM) mimicking a 3D microenvironment is an essential requirement to achieve desirable repair or regeneration of damaged tissue or organ. In this context, hydrogels may be able to create an appropriate 3D microenvironment. The lack of mechanical stability limits their application. This study prepared and characterized thermosensitive injectable hydrogels based on chitosan and polygalacturonic acid (PgA). A method of producing novel biomimetic polymeric-based injectable hydrogel using hydrothermal assisted hydrolysis is introduced. The synthesized hydrogels showed good compressive stiffness. We have also studied the possible chemistry of the materials in the hydrogel network. The biocompatibility and gelation time of the hydrogel was optimized by adding β-glycerophosphate (βGP) and hydroxyapatite. The synthesized liquid formulation can turn into gel at 37 °C. The biocompatibility for MG63 cells within 3D hydrogels was investigated. Scanning electron microscopy revealed that the PEC fibers are uniformly distributed in the hydrogel matrix. MTT assay and confocal imaging were employed to observe cytotoxicity and proliferation of cells cultured in the hydrogels with and without an osteogenic medium. Alkaline phosphatase activity (ALP) and collagen production in cell-cultured hydrogel were also measured to evaluate osteoblast activity. The cellular responses to various types of hydrogels cultured at a 14-day culture appeared to be superior in the hydrogels with gelatin incorporated and hydrothermally treated PEC fibers. These results indicated that hydrothermal treatment and inclusion of gelatin in the chitosan-βGP hydrogel system enhanced the hydrogel bioactivity and mechanical properties. Overall, improved cellular proliferation, osteogenic differentiation, and stable physical network with uniform distribution of fibrous matrix in-vitro were achieved. Graphical abstract: Unlabelled Image